Pola Pertumbuhan Akar Timun di Polybag: Implikasinya pada Penyerapan Nutrisi dan Ketahanan Hidup - Perti Citra Damarni Waruwu; Della Howu Howu Zendrato; Joy Blesswan Endiyanti Mendrofa; Karisman Putra Gulo; Natalia Kristiani Lase (Flora : Jurnal Kajian Ilmu Pertanian dan Perkebunan, 2025)
This study aims to explore the root growth patterns of cucumber (Cucumis sativus L.) cultivated in a polybag system, and examine the implications for nutrient absorption efficiency and plant survival. The method used was a systematic literature review, with narrative analysis of recent studies in the last five years. Data were analyzed to identify the relationship between root architecture, growing medium, and nutrient absorption efficiency. The results showed that the polybag system, with its limited root growing space, promoted adaptation of root growth patterns, including an increase in lateral root density and a reduction in primary root length. Coconut fiber- and vermiculite-based growing media were shown to increase nutrient absorption capacity by up to 30%, while inoculation of rhizosphere microorganisms, such as mycorrhiza, increased phosphorus use efficiency by up to 25%. In addition, optimal root zone temperature plays an important role in supporting root metabolic activities. The conclusion of this study confirms that optimizing root growth patterns through growing media, temperature management, and utilization of microorganisms can significantly increase the productivity of cucumber plants. These findings provide a basis for developing more efficient and sustainable cultivation strategies in modern horticultural systems.